(untitled) (Afaq Lughawiyyah, 2024)
This research investigates the comparative effectiveness of electronic and printed dictionaries in expanding Arabic vocabulary among Arabic Language and Literature students at International Islamic University Malaysia. The study aims to determine the impact of these two dictionary formats on vocabulary acquisition, depth of word knowledge, and the ability to utilize newly acquired vocabulary in diverse linguistic contexts. By examining factors such as ease of use, access to multiple word forms, and the availability of contextual information, this study seeks to identify the strengths and weaknesses of each dictionary type. Ultimately, the research aims to provide evidence-based recommendations for optimizing Arabic vocabulary development through the effective use of dictionary resources. This study followed a survey analysis approach to evaluate the effectiveness of using electronic and printed dictionaries in enhancing Arabic vocabulary among students of the Department of Arabic Language and Literature at the International Islamic University Malaysia. Data were collected through questionnaires distributed to a sample of students to gather their opinions and experiences with both the electronic and printed dictionaries. Results indicated that electronic dictionaries significantly enhanced vocabulary acquisition through quick access and interactive features, while printed dictionaries were preferred for in-depth word study and academic analysis.